Nanowire conductance biosensor by spacer patterning lithography technique for DNA hybridization detection: Design and fabrication method - Uda, Hashim, Prof. Dr.; Shahrir, Salleh; Emi, Azri Shohini; Siti Fatimah, Abd Rahman (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://www.ieee.org/